N‐Functionalised Imidazoles as Stabilisers for Metal Nanoparticles in Catalysis and Anion Binding. Issue 6 (8th June 2020) - Serpell, Christopher J.; Cookson, James; Beer, Paul D.
Abstract: Metal nanoparticles (NPs) have physicochemical properties which are distinct from both the bulk and molecular metal species, and provide opportunities in fields such as catalysis and sensing. NPs typically require protection of their surface to impede aggregation, but these coatings can also block access to the surface which would be required to take advantage of their unusual properties. Here, we show that alkyl imidazoles can stabilise Pd, Pt, Au, and Ag NPs, and delineate the limits of their synthesis. These ligands provide an intermediate level of surface protection, for which we demonstrate proof‐of‐principle in catalysis and anion binding. Abstract : Protecting the surface : Imidazole ligands offer a potentially useful intermediate level of stabilisation for metal nanoparticles. We outline the parameters required for synthesis of such nanoparticles and provide two case studies for their application, in catalysis and in sensing.